PENINGKATAN HOTS DALAM PEMBELAJARAN BAHASA INDONESIA MELALUI MODEL PEMBELAJARAN BERBASIS MASALAH (PROBLEM BASED LEARNING) DI IAKN MANADO - Yolanda Nany Palar (The Way Jurnal Teologi dan Kependidikan, 2020)
This research aims to improve HOTS (High Order Thinking Skill) in learning Indonesian through the Problem Based Learning Model at IAKN Manado. This research uses descriptive qualitative analytic method. Based on the research results obtained (1) Problem-based learning model (PBM) is a learning model that requires students to think critically and creatively in answering or solving problems related to learning Indonesian language. The problem is related to language skills, including listening, speaking, reading, and writing, but is more focused on productive skills, which are speaking and writing. In applying this model, students become active, creative, and critical in solving problems. (2) Critical and creative attitude in solving problems in learning Indonesian language can directly improve the high-level thinking skills (HOTS) of IAKN Manado students. That means HOTS (High Order Thinking Skill) or the ability to think at a higher level is one of the skills or abilities that students need to have in finding solutions to the problems offered in learning Indonesian language. Problem Based Learning Model is one of the learning models that can improve HOTS. Conclusion: Based on the results of the analysis related to the development of student ability as evidenced by the initial test, test cycle 1, and test cycle 2. In the initial test, the score is dominated by score 1 with an interval of 0-39 reached a percentage of 48%, while a score 4 with an interval of 85-100 reached 0%. At the end of cycle 1, an increase in score 4, which increased to 15%, while score 1 decreased to 7% and the same result applies to the end value of cycle 2. In cycle 2 the score 4 continued to increase and reached a percentage of 30%. The data shows that the application of the problem based learning model in the Indonesian Language course at IAKN Manado was able to improve higher order thinking skills (HOTS). Suggestions: 1) Problem-based learning model is able to encourage students to develop and improve critical and creative thinking skills in efforts to solve problems. This shows that the application of problem based learning model can improve higher order thinking skills (HOTS). 2) Problem-based learning model is able to improve the ability to think at a higher level (HOTS) which is portrayed through an increasingly critical and creative way of thinking and encourage all the potentials in students. In addition, problem-based learning can increase the courage of students so that they are automatically active in learning activities. Problem-based learning model can be used in learning Indonesian language and other subjects as well.